Utilization of sugarcane bagasse fibers for the manufacture of bio-composite panel / Junaiza Ahmad Zaki, Suhaimi Muhammed and Nor Suhaina Shahidan - Ahmad Zaki, Junaiza; Muhammed, Suhaimi; Shahidan, Nor Suhaina (2012)
Agricultural waste such as sugarcane bagasse is abundant in Malaysia and at present is mainly used as combustible material for energy supply in the sugar factory. This study was conducted with the aim to investigate the possibility of manufacturing bio- composite panel from sugarcane bagasse at three different density levels namely (450 kgm-3 , 550 kgm-3 and 650 kgm-3 , two amount of resin contents such as 10 and 12% and with the addition of 1% wax or without wax addition. The panels produced were tested for mechanical properties such as Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) and physical properties namely water absorption (WA) and thickness swelling (TS) conforming to the European Standards (EN 310). The results revealed that those panels with board density 650 kgm-3 gave superior mechanical strength (MOE value of 1152.06 MPa) and board density of 450 kgm-3 (MOE value of 545. 15MPa). An increase in the amount of resin content from 10% and 12% resulted in the increment of MOE value from 1082 MPa to 1114 MPa. The addition of 1% wax helped to improve the water absorption (decreasing from 52% to 42%) and thickness swelling (decreasing from 27% to 24%) of the bio- composite panels. Thus, it can be concluded from the above findings that bio-composite panel can be successfully manufactured from sugarcane bagasse as the potential source of raw material from agriculture waste.